Determining Promotions at UD. Jakarta Pixel using Web-Based FP-Growth Association Model - Potale, Lisa Elisia; Ahmad, Muhammad Sabri; Khairan, Amal (Department of Informatics, Faculty of Da'wah, UIN Saizu Purwokerto, 2025)
In the rapidly advancing digital era, the growth of e-commerce has significantly transformed the retail business paradigm. However, physical stores still play a crucial role in providing direct and personal experiences to customers. UD. Jakarta Pixel, a physical store specializing in photography and electronic products, faces increasingly intense competition from various e-commerce platforms. To remain competitive, sophisticated and effective promotional strategies are required. This research uses the FP-Growth association model as the method to determine effective website-based product promotions at UD. Jakarta Pixel. The research results indicate that the FP-Growth algorithm successfully analyzes customer purchasing patterns, identifies relationships between frequently purchased products, and enables the store to design more targeted promotions according to customer preferences. Implementing this system not only enhances operational efficiency in data analysis but also provides accurate information for strategic decision-making, optimizing product promotion strategies, and ultimately increasing sales. In conclusion, the application of the FP-Growth algorithm at UD. Jakarta Pixel is an innovative solution that strengthens the competitiveness and sustainability of physical stores amid the rapid growth of e-commerce, leveraging transaction data analysis for more effective and efficient promotion planning.